Agronomic performance and selection of green super rice doubled haploid lines from anther culture - SITI NURHIDAYAH; BAMBANG SAPTA PURWOKO; ISWARI SARASWATI DEWI; WILLY BAYUARDI SUWARNO; ISKANDAR LUBIS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nurhidayah S, Purwoko BS, Dewi IS, Suwarno WB, Lubis I. 2023. Agronomic performance and selection of green super rice doubled haploid lines from anther culture. Biodiversitas 24: 819-826. Rice is the staple food of most Asian, including Indonesian people. Plant breeding plays an important role in producing high-yielding varieties of rice to meet national carbohydrate sufficiency. Green Super Rice (GSR) is an alternative for rice variety development that has the advantages of high yield, good quality, pest resistance, and efficient fertilizer use to support sustainable agriculture. This study aimed to evaluate the agronomic character of GSR doubled haploid (DH) lines derived from anther culture and determine the best GSR rice lines based on index selection. The treatment was 65 genotypes consisting of 60 DH of GSR lines from anther culture of 5 combinations of crosses and 5 check varieties. The study used a randomized complete block design with three replications. The results showed that most of the tested lines had similar agronomic performances to the check variety Inpari 42 Agritan GSR. Almost all agronomic characters of the GSR DH lines had high genetic variability. Most characters had a high category of broad-sense heritability except panicle length. Line selection using index selection for economically important agronomic characters yielded 27 GSR DH lines having high productivity, number of productive tillers per hill, number of total grains per panicle, and percentage of filled grains per panicle.